Pengaruh Model Pembelajaran Hibrid Terhadap Kemampuan Komunikasi Matematika Pada Sekolah Menengah Pertama Negeri 1 Curup Tengah - Bainamus , Putri Milanda; Hartanto; Abdullah, M. Ilham (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2017)
This research aims to determine the influence of hybrid learning model to communication mathematics junior high school students. This research is a quantitative with experimental methods in the form of pure experiment types. The population were all eighth grade students at Public Junior High School 1 of Middle Curup, Rejang Lebong Regency, Bengkulu Province in 2015/2016. The number of samples uses 37 persons as experimental class and 35 persons as control class. This research is a pure experiment using a pretest-posttest control group. In this study, the data collection method used is the testing techniques. Based on the analysis can be concluded that there is a significant effect on communications hybrid learning model mathematics junior high school student.